SAR and characterization of non-substrate isoindoline urea inhibitors of nicotinamide phosphoribosyltransferase (NAMPT). Issue 15 (1st August 2017) - Curtin, Michael L.; Heyman, H. Robin; Clark, Richard F.; Sorensen, Bryan K.; Doherty, George A.; Hansen, T. Matthew; Frey, Robin R.; Sarris, Kathy A.; Aguirre, Ana L.; Shrestha, Anurupa; Tu, Noah; Woller, Kevin; et al.
Graphical abstract: Abstract: Herein we disclose SAR studies that led to a series of isoindoline ureas which we recently reported were first-in-class, non-substrate nicotinamide phosphoribosyltransferase (NAMPT) inhibitors. Modification of the isoindoline and/or the terminal functionality of screening hit5 provided inhibitors such as52 and58 with nanomolar antiproliferative activity and preclinical pharmacokinetics properties which enabled potent antitumor activity when dosed orally in mouse xenograft models. X-ray crystal structures of two inhibitors bound in the NAMPT active-site are discussed.